Anthropometric cut-offs to identify hyperglycemia in an Afro-Caribbean population: a cross-sectional population-based study from Barbados. Issue 1 (16th August 2021) - Wade, Alisha N; Hambleton, Ian R; Hennis, Anselm J M; Howitt, Christina; Jeyaseelan, Selvi M; Ojeh, Nkemcho O; Rose, Angela M C; Unwin, Nigel
Abstract : Introduction: Body mass index (BMI) and waist circumference (WC) cut-offs associated with hyperglycemia may differ by ethnicity. We investigated the optimal BMI and WC cut-offs for identifying hyperglycemia in the predominantly Afro-Caribbean population of Barbados. Research design and methods: A cross-sectional study of 865 individuals aged ≥25 years without known diabetes or cardiovascular disease was conducted. Hyperglycemia was defined as fasting plasma glucose ≥5.6 mmol/L or hemoglobin A1c ≥5.7% (39 mmol/mol). The Youden index was used to identify the optimal cut-offs from the receiver operating characteristic (ROC) curves. Further ROC analysis and multivariable log binomial regression were used to compare standard and data-derived cut-offs. Results: The prevalence of hyperglycemia was 58.9% (95% CI 54.7% to 63.0%). In women, optimal BMI and WC cut-offs (27 kg/m 2 and 87 cm, respectively) performed similarly to standard cut-offs. In men, sensitivities of the optimal cut-offs of BMI ≥24 kg/m 2 (72.0%) and WC ≥86 cm (74.0%) were higher than those for standard BMI and WC obesity cut-offs (30.0% and 25%–46%, respectively), although with lower specificity. Hyperglycemia was 70% higher in men above the data-derived WC cut-off (prevalence ratio 95% CI 1.2 to 2.3). Conclusions: While BMI and WC cut-offs in Afro-Caribbean women approximate international standards, our findings, consistent with other studies, suggest lowering cut-offs in men may be warranted to improve detection of hyperglycemia. Our findings do, however, require replication in a new data set.